Preliminary data on help‐seeking intentions and behaviors of individuals completing a widely available online screen for eating disorders in the United States. Issue 9 (16th June 2020) - Fitzsimmons‐Craft, Ellen E.; Balantekin, Katherine N.; Graham, Andrea K.; DePietro, Bianca; Laing, Olivia; Firebaugh, Marie‐Laure; Smolar, Lauren; Park, Dan; Mysko, Claire; Funk, Burkhardt; Taylor, C. Barr; Wilfley, Denise E.
Abstract: Objective: Scaling an online screen that provides referrals may be key in closing the treatment gap for eating disorders (EDs), but we need to understand respondents' help‐seeking intentions and behaviors after receiving screen results. This study reported on these constructs among respondents to the National Eating Disorders Association online screen who screened positive or at high risk for an ED. Method: Respondents completed the screen over 18 months (February 9, 2018–August 28, 2019). Those screening positive or at high risk for an ED ( n = 343, 072) had the option to provide data on help‐seeking intentions (after screen completion) and behaviors (2‐month follow‐up). Results: Of eligible respondents, 4.8% ( n = 16, 396) provided data on help‐seeking intentions, with only 33.7% of those reporting they would seek help. Only 7.6% of eligible respondents opted in to the 2‐month follow‐up, with 10.6% of those completing it ( n = 2, 765). Overall, 8.9% of respondents to the follow‐up reported being in treatment when they took the screen, 15.5% subsequently initiated treatment, and 75.5% did not initiate/were not already in treatment. Discussion: Preliminary results suggest that among the small minority who provided data, only one‐third expressed help‐seeking intentions and 16% initiated treatment. Online screening should consider ways to increase respondents' motivation for and follow‐through with care.